Public Procurement versus Laissez-Faire: Evidence from Household Waste Collection. (20th February 2019) - Meriläinen, Jaakko; Tukiainen, Janne
Abstract: We document that switching from laissez-faire production to public procurement in residential waste collection in Finland reduces the number of firms active in the local market, but induces a statistically significant and large decrease in unit prices on average. While public procurement, thus, seems to be desirable from the citizens' perspective, not all municipalities adopt public procurement. We provide descriptive evidence that municipal council composition is associated with the chosen regime. This suggests that local politics may be one obstacle for the efficient provision of local public goods. (JEL codes: C23, D72, H76, L13, and L85).